First Report of Polyplax spinulosa in Albino Rats in Banyuwangi, East Java, Indonesia - Kusuma, Widya Ayu; Yudhana, Aditya; Andriyani, Anita; Oktaviana, Vivi; Chaerunisa, Nadya Amanda (Jurnal Medik Veteriner, 2020)
Albino rats (Rattus norvegicus) is one animal that is often used by researchers in the laboratory. Albino laboratory rats were found to have symptoms of hair loss, the hair is dirty, and itching at the base of the tail and found ectoparasites. Department of Parasitology in Banyuwangi PSDKU Airlangga University have observed and identified ectoparasites as the cause of the symptoms of these rats. Albino rats infested Polyplax spinulosa.